Komunikasi Multikultural Pada Era Teknologi - Mochamad Rosy Ilhamsyah (Al-Maquro' : Jurnal Komunikasi dan Penyiaran Islam, 2020)
This paper about background, objectives and benefits of studying multicultural communication in the technological era, including three focus issues, namely: First, what lies behind studying multicultural communication. Second, What are the objectives of studying multicultural communication? Finally, what are the benefits of studying multicultural communication? To answer questions about this problem completely and deeply, the writer uses descriptive analysis method. It can be found: firstly, the background examines multicultural communication that presents communication and transportation technology, overcomes global difficulties, mutation acceleration, mobility, global rural transport, and the development of the world political economy on the dynamics and future of Indonesia. Secondly, the aim of studying multicultural communication is peaceful coexistence, global understanding, and the reduction of respectable aggressiveness. Finally, the benefits of studying communication are three perspectives.